A Comparative Study on Treatment of Diabetic Foot Infection by Acetic Acid, Rifocin and Probiotics - AL-SHaibani, aAbdulwahd B.; AL-Mukhtar, Sadeq A.; Resn, Noorhan Sabih (AL-Kindy College Medical Journal, 2014)
Introduction: Diabetic foot infections are one of the most severe complications of diabetes. This study was aimed to determine the common bacterial isolates of diabetic foot infections and the in vitro antibiotic susceptibility then treatment.Methods: A swab was taken from the foot ulcer, and the aerobic bacteria were isolated and identified by cultural, microscopic and biochemical test, then by api-20E system. After that their antibiotic susceptibility pattern was determined. Then local and systemic treatment was used to treat the diabetic foot patients.Results: Bacterial isolates belonging to twelve species were obtained from diabetic foot patients. Gram (-) bacteria were the predominant pathogens in the diabetic foot infections, high percentage recorded by Klebsiella pneumoniae (25.71%). Polymicrobial infection was observed in 72% patients. Imipenem was the most affected antibiotic in susceptibility test, except for Acinetobacter spp. that resist for all antibiotic used, followed by amikacin and ciprofloxacin. Local treatment gave more inhibitory effect on diabetic foot infections than the systemic treatment.Conclusion: High prevalence of multi-drug resistant pathogens was observed. Gram (-) bacteria especially Klebsiella pneumoniae was the predominant pathogens in the diabetic foot infections, and Staphylococcus aureus was the most common of Gram (+) bacteria. Local treatment was the best for treatment of diabetic foot infection patients.